Poetry, Prose, Drama: Various Expressions in Literature - Komala, Imas; Queena Hadi Putri, Nina (Sahabat Publikasi, 2025)
Literature serves as a powerful medium for expressing human emotions, ideas, and experiences, with poetry, prose, and drama being the three primary genres. These genres are distinct in their characteristics, narrative structures, and techniques used to convey their messages. The purpose of this study is to explore the diverse expressions within poetry, prose, and drama, and to understand how they reflect and engage with the complexities of human life and society. A descriptive qualitative research method was applied, involving literature review, data collection from classical and modern literary works, and secondary sources such as theory books and journals. The results show that each genre uniquely portrays emotions, social issues, and human conflicts—poetry using symbolic language and rhythm, prose offering detailed narrative descriptions, and drama expressing tension through dialogue and performance. This study concludes that understanding the expressive qualities of these literary genres enhances our comprehension of human life, culture, and societal values, emphasizing their ongoing relevance in addressing contemporary issues.